Kultivierungsmaßnahmen in der albanischen Landwirtschaft.: Anmerkungen zu einer neu erstellten Karte - Toepfer, Helmuth (ERDKUNDE, 1991)
The map of Albania presented here shows that almost all areas up to 100 m above sea-level, as well as all the major valley openings in the highlands, have been included in irrigation schemes, and that a large proportion of the agriculturally utilized area has been terraced. Apart from some minor areas, these measures of improvement only date from after 1944. However, as Albania presents the highest rates of population increase in Europe, and the agricultural policy of the country led to the wasting of capital, under-employment, poor production structure, and an increase in regional disparities, the supply situation in the country has steadily deteriorated since 1980.